Synthesis and Antibacterial Activities of Aspirin-Chalcone Derivatives - Phang, Sai Foong. (Universiti Malaysia Sarawak (UNIMAS), 2015)
In recent years, chalcone and its derivatives have been studied extensively in terms of their biological activities. In this study, the synthesis and characterization of aspirin-chalcone derivatives has been carried out. A series of aspirin-chalcone derivatives were successfully synthesized from the reaction of intermediates 31a-c with acetylsalicyloyl chloride to yield final product of 32a-c with overall yield of 21.8 % to 88.4 %. All the derivatives were characterized by FT-IR, 1HNMR and 13CNMR. Disc diffusion method was then used to study the antibacterial activities of the new series. All of them showed the results of poor antibacterial properties. The structure that affected the strength of antibacterial properties was discussed.